El ordenamiento territorial instrumento de integracion, competencia y desarrollo - Cruz Reyes, Fray Masias (2005)
Peru is geographically a heterogeneous contry; with uneven reliefs and very varied geoformas that determine its climatic variety, with ecosystems and an unique biodiversity in the world, In this sense, the territory's ways occupation by man was given in a spontaneous and circumstantial way, generating chaos and imbalance in the national territory occupation, that's for one side; for the other; for the other; the State; hasn´t advanced since the delimitations of the districts politican administrative don´t reflect the geographical reality and less the society interest´and comes generating bordering conflicts among districts, provinces and competitive and developed country and to achieve it should be opted as politics of State the territorial classification as instrumenr of physical Planning at national, regional, micro-regional and local level.